Azerbaijan Republic : Poverty Assessment, Volume 1. Summary and Conclusions - World Bank (Washington, DC, 2013)
Poverty remains a major challenge in Azerbaijan, where income poverty is spread throughout the country. This Poverty Assessment reviews available household data, which suggest particular demographic characteristics of the poor - no significant differences in the poverty rate by gender of the household head were recorded. However, the report conveys the internally displaced people, are a core group of particularly vulnerable people, heavily dependent on state transfers, and donor assistance. Moreover, there are serious concerns about the non-income indicators of poverty, including the quality of health care, and education, as well as access to basic services. The report however highlights that the macroeconomic outlook for Azerbaijan is positive, and, it should be possible to achieve significant impact on poverty over the next ten years, provided appropriate policies are followed. The oil and gas windfall should be a major benefit, contributing to lasting poverty reduction, and raising incomes. The strategy for poverty reduction stipulates the need for increased employment rates, and productivity in the non-oil economy, accompanied by measures to strengthen, and improve the provision of basic services, and infrastructure. Likewise, a well-targeted social assistance provision for vulnerable groups should be considered, if a sustaining economic growth is to be attained, to be accompanied by targeted programs, focused on education and health programs. In addition, positive economic growth should be based on a vibrant private sector, resulting from a more liberal business environment, improved financial intermediation and credit availability to the enterprise sector, supported by a clear legal framework, and implementation of the privatization program, to enhance investments in human and physical capital. Regarding the rural sector, while the strategy should aim at improving the incomes of the rural population, it should however emphasize the development of non-agricultural activities, i.e., food processing, and services in rural areas.